Effects of different positive end-expiratory pressure titration strategies on mechanical power during ultraprotective ventilation in ARDS patients treated with veno-venous extracorporeal membrane oxygenation: a prospective interventional study - Bösing, Christoph; Schäfer, Laura Sophie; Graf, Peter Tobias; Pelosi, Paolo; Rocco, Patricia R. M.; Lücke, Thomas; Krebs, Jörg (Journal of critical care, 2024)
Purpose - Ultraprotective ventilation in acute respiratory distress syndrome (ARDS) patients with veno-venous extracorporeal membrane oxygenation (VV ECMO) reduces mechanical power (MP) through changes in positive end-expiratory pressure (PEEP); however, the optimal approach to titrate PEEP is unknown. This study assesses the effects of three PEEP titration strategies on MP, hemodynamic parameters, and oxygen delivery in twenty ARDS patients with VV ECMO. - Material and methods - PEEP was titrated according to: (A) a PEEP of 10 cmH2O representing the lowest recommendation by the Extracorporeal Life Support Organization (PEEPELSO), (B) the highest static compliance of the respiratory system (PEEPCstat,RS), and (C) a target end-expiratory transpulmonary pressure of 0 cmH2O (PEEPPtpexp). - Results - PEEPELSO was lower compared to PEEPCstat,RS and PEEPPtpexp (10.0 ± 0.0 vs. 16.2 ± 4.7 cmH2O and 17.3 ± 4.0 cmH2O, p < 0.001 each, respectively). PEEPELSO reduced MP compared to PEEPCstat,RS and PEEPPtpexp (5.3 ± 1.3 vs. 6.8 ± 2.0 and 6.9 ± 2.3 J/min, p < 0.001 each, respectively). PEEPELSO resulted in less lung stress compared to PEEPCstat,RS (p = 0.011) and PEEPPtpexp (p < 0.001) and increased cardiac output and oxygen delivery (p < 0.001 each). - Conclusions - An empirical PEEP of 10 cmH2O minimized MP, provided favorable hemodynamics, and increased oxygen delivery in ARDS patients treated with VV ECMO. - Trial registration - German Clinical Trials Register (DRKS00013967). Registered 02/09/2018https://drks.de/search/en/trial/DRKS00013967